(untitled) (SADGAMAYA, 2026)
The ever-changing technology and human behavior have awakened the leaders to change the way they lead their subordinates. This study aims to examine leaders’ art of influencing their subordinates in the IT sector using transformational, transactional, laissez-faire, and servant leadership styles, and to determine which best suits employees’ job satisfaction in the IT industry. The study followed a causal research design with snowball sampling, approaching 400 respondents involved in the IT sector within Kathmandu Valley, and adopted quantitative measures to analyze the influence of leadership styles on job satisfaction. The multiple regression analysis revealed that servant leadership (β = 0.494, p< 0.01) most strongly predicted job satisfaction among IT professionals, followed by laissez-faire leadership (β = 0.233, p < 0.01), transformational leadership (β = 0.162, p < 0.01), and transactional leadership (β = 0.082, p < 0.01). Servant leadership that promotes a sense of fellowship and independence and minimizes unnecessary interference appears to affect IT workers’ satisfaction levels positively. Respondents from the Kathmandu Valley only, and the relations between leadership styles and job satisfaction, were the limitations of this study. However, policymakers, organizational leaders, and HR practitioners can use the study’s evidence-based insights to develop more effective leadership development programs and foster more fulfilling, productive workplaces. This research makes a distinctive contribution to the limited empirical literature on leadership styles in Nepal’s expanding IT industry. The study offers insights into the leadership style that most effectively improves employee morale and retention, focusing on the public and private IT sectors within a dynamic technological and cultural context